Coordination between crew members on flying multihulls: A case study on a Nacra 17 - Terrien, E.; Huet, B.; Iachkine, P.; Saury, J. (Journal of Sports Science & Medicine, 2020)
A current trend in sailing sports is the use of boats equipped with hydrofoils, allowing the boats to "fly" over the water surface. In this situation, the handling of the boat requires fine coordination between the crew members to maintain the precarious flight. The purpose of this case study was to analyze the crew activity on a flying multihull and explore the role of the shared sport equipment in the emergence of coordination between crew members. Data were collected during a training session with a crew of expert sailors. A joint analysis of phenomenological and mechanical data was conducted. The aim of the analysis was to categorize the forms of interactions between crew members, boat and environment. Results showed that collective coordination in the studied situation involves six forms of interaction that are associated with stable, unstable or critical states of the flight. Consequently, we discussed the role played by the crew members, the behavior of the boat and the environment in the collective coordination.